What Do We Know About Namibia's Competitiveness? - Miyajima, Ken (IMF Working Papers; Working Paper ;, 2007)
This paper evaluates Namibia's competitiveness using several traditional indicators; it concludes that, while the real effective exchange rate (REER) is in equilibrium at present?suggesting no imminent need for concern?the country may wish to improve its competitiveness by increasing educational attainment, reducing the skills mismatch, and diversifying its exports. Moreover, although Namibia scores relatively well on survey-based major indicators of structural competitiveness, the business environment can be made more conducive to private sector activity.